AN EXPERIMENTAL RESEARCH REGARDING THE OPTIMUM COMPOSITION FOR WOOD SLAG BOARDS - Mihajlova, Julia (International Journal of Engineering Technologies and Management Research, 2019)
Wood slag boards (WSB) belong to the group of composites formed on the basis of mineral binders (cement, gypsum, blast-slag, etc.). They are multi-componential systems consisting of wood particles, slag-alkaline and mineralizator. The physico-mechanical properties of WSB completely answer the standard requirements valid for high-density wood-cement boards and therefore can be used as a competitive building material. The economic relevancy of their production is grounded in providing building industry with high-quality and at the same time cheap materials, as well as in utilizing scrap materials which would otherwise pollute the environment (blast slag and scrap wood). The optimizing of the mass parts of the components of WSB is a very important problem both from technological and economical point of view. The success in solving the optimizing problem depends to a great degree on the choice of method. This is way a planned experiment is applied, based on the simplex method for multicomponent system with preliminarily determined limits of calculation of the factors. With the help of specialized computer software, the optimum quantity of the components is determined through graphically presented optimum areas